CRUX: a creativity and user experience model. Issue 2 (3rd April 2021) - Fleury, Sylvain; Vanukuru, Rishi; Mille, Charles; Poinsot, Killian; Agnès, Aurélien; Richir, Simon
ABSTRACT: The field of Virtual Reality has been developing at a steady pace, and VR is finding new uses as a support for creative tasks. The objective of this study is to propose a theoretical model describing the links between user experience and creativity. Pre-existing theoretical links have been identified in relevant scientific literature. Two experiments were then conducted in order to identify new links and replicate results. These experiments involved respectively 76 and 42 participants who individually performed a task requiring divergent creativity using virtual reality drawing tools. The results indicate that cybersickness leads to a decrease in fluency, i.e. the number of ideas generated, but also shades the links between flow and the relevance of the ideas generated. On the basis of this result, we propose the CRUX model to lead to recommendations for the design of tools and simulations to support divergent creativity.